Spaces for paws to prowl : fulfilling social needs through the furry fandom’s subcultural identity, practices, and the benefits that follow - Tan, Ai-Ling (2019)
As a participatory culture and subculture, the furry fandom is a site where psychological and social needs can be fulfilled, in particular the need to feel belongingness to a group and escape from routine life. However, as with other male-dominant subcultures, hegemonic masculinity and marginalization may affect female members’ ability to feel welcome and that they belong. Through participant observation, in-depth interviews and an overarching autoethnographic approach, this research explores how the male-dominant furry fandom in Singapore provides a safe space for freedom of self-expression and exploration, how its subcultural practices can be at once functional in fulfilling social needs while also creating situations that marginalize the female minority, and how sustained engagement with the furry fandom can result in learning transferable skills like communication and empathy which are useful in non-fandom settings.